Desvio do periélio de Mercúrio na relatividade geral - Silva, Ana Luiza Bastos Barbosa Guimarães da [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This work's objective is to explicit all the steps taken by Einstein so that he could solve the precession of the perihelion of Mercury and find its orbital deflection (the contribution the Special Relativity has given to solve the Newtonian mechanics approach). The first step was to use the Special Relativity, in a plane metric, where the Lorentz Transformations are valid, then define a tensor notation and its properties. While going to the General Relativity, the two body problem approach is made, therefore an accelerated moving reference frame with respect to a steady one are treated in a curve metric, and that will be a Schwarzschild metric approach in this work. Calculations are developed and considerations made to obtain the geodesic curves to the Sun-Mercury sistem from the Euler-Lagrange equations, so that the orbital deflection can be acquired and the exact shape that Mercury's orbit takes in the precession while rotating around the Sun. Finally, the MATLAB platform was used in order to get the numerical solution for the problem, and specific cases were studied to get the validation and a comparison made with the analitical solution

Este trabalho tem como objetivo explicitar todos os passos que Einstein tomou para que pudesse resolver o problema da precessão do periélio de Mercúrio e encontrar seu desvio orbital (a contribuição que a Relatividade Geral deu para corrigir a abordagem da mecânica Newtoniana). O primeiro passo foi utilizar a Relatividade Especial, numa métrica plana, onde as transformações de Lorentz são válidas, e definir a notação tensorial e suas propriedades. Ao passar para a Relatividade Geral, o problema de dois corpos é abordado, que consequentemente trata de um referencial acelerado e outro inercial numa métrica curva, que neste trabalho será adotada a métrica de Schwarzschild. Cálculos são desenvolvidos e considerações feitas para a obtenção das curvas geodésicas para o sistema Sol-Mercúrio a partir das equações de Euler-Lagrange, para que possa obter o desvio orbital e a forma que a órbita de Mercúrio toma com a precessão em sua rotação em torno do Sol. Por fim, foi utilizada a plataforma MATLAB para a obtenção da solução numérica do problema e casos foram estudados para sua validação e comparação com a solução analítica obtida
Deviation of the perihelion of Mercury in general relativity
Keywords: Relatividade; Astrofisica; Mercúrio; Mercury